Evaluating Growth Performance and Feed Cost Economics of Japanese Quails Fed with Varying Levels of Guar Meal - Guntaka,; Kumar Chitithoti, Anil; Kishore Konka, Raja; Thullimalli, Susmita; Suratani, Sreedhar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A study was conducted to evaluate the inclusion of guar meal (GM) as a partial replacement for soybean meal (SBM) in Japanese quail  diets. 150-day-old chicks were randomly assigned to five dietary treatments: T1 (0% GM), T2 (2% GM), T3 (4% GM), T4 (6% GM) and T5 (8%  GM), with three replicates per treatment (10 birds each). Feed intake, body weight gain (BWG), and feed conversion ratio (FCR) were  recorded weekly, and cost-effectiveness was assessed based on current local market prices. Results revealed that BWG significantly  improved (p0.05). FCR was significantly better (p
Keywords: Cost economics; Feed efficiency; Growth performance; Guar meal; Japanese Quails